Macrophage-derived macrophage migration inhibitory factor mediates renal injury in anti-glomerular basement membrane glomerulonephritis - Yang, Hui; Li, Jinhong; Huang, Xiao-ru; Bucala, Richard; Xu, Anping; Lan, Hui-Yao (Frontiers in Immunology, 2024)
Macrophages are a rich source of macrophage migration inhibitory factor (MIF). It is well established that macrophages and MIF play a pathogenic role in anti-glomerular basement membrane crescentic glomerulonephritis (anti-GBM CGN). However, whether macrophages mediate anti-GBM CGN via MIF-dependent mechanism remains unexplored, which was investigated in this study by specifically deleting MIF from macrophages in MIF f/f-lysM-cre mice. We found that compared to anti-GBM CGN induced in MIF f/f control mice, conditional ablation of MIF in macrophages significantly suppressed anti-GBM CGN by inhibiting glomerular crescent formation and reducing serum creatinine and proteinuria while improving creatine clearance. Mechanistically, selective MIF depletion in macrophages largely inhibited renal macrophage and T cell recruitment, promoted the polarization of macrophage from M1 towards M2 via the CD74/NF-B/p38MAPK-dependent mechanism. Unexpectedly, selective depletion of macrophage MIF also significantly promoted Treg while inhibiting Th1 and Th17 immune responses. In summary, MIF produced by macrophages plays a pathogenic role in anti-GBM CGN. Targeting macrophage-derived MIF may represent a novel and promising therapeutic approach for the treatment of immune-mediated kidney diseases.